Maturation of neuronal AD-tau pathology involves site-specific phosphorylation of cytoplasmic and synaptic tau preceding conformational change and fibril formation. - Aragão Gomes, L.; Uytterhoeven, V.; Lopez-Sanmartin, D.; Tomé, S.O.; Tousseyn, T.; Vandenberghe, R.; Vandenbulcke, M.; von Arnim, C.A.F.; Verstreken, P.; Thal, D.R. (Acta Neuropathologica, 2021)
In Alzheimer's disease (AD), tau-protein undergoes a multi-step process involving the transition from a natively unfolded monomer to large, aggregated structures such as neurofibrillary tangles (NFTs). However, it is not yet clear which events initiate the early preclinical phase of AD tauopathy and whether they have impact on the propagation of tau pathology in later disease stages. To address this question, we analyzed the distribution of tau species phosphorylated at T231, S396/S404 and S202/T205, conformationally modified at the MC1 epitope and fibrillary tau detected by the Gallyas method (Gallyas-tau), in the brains of 15 symptomatic and 20 asymptomatic cases with AD pathology as well as of 19 nonAD cases. As initial tau lesions, we identified phosphorylated-T231-tau diffusely distributed within the somatodendritic compartment (IC-tau) and phosphorylated-S396/pS404-tau in axonal lesions of the white matter and in the neuropil (IN-tau). The subcellular localization of pT231-tau in the cell body and pS396/pS404-tau in the presynapse was confirmed in hP301L mutant Drosophila larvae. Phosphorylated-S202/T205-tau, MC1-tau and Gallyas-tau were negative for these lesions. IC- and IN-tau were observed in all analyzed regions of the human brain, including early affected regions in nonAD cases (entorhinal cortex) and late affected regions in symptomatic AD cases (cerebellum), indicating that tau pathology initiation follows similar processes when propagating into previously unaffected regions. Furthermore, a sequence of AD-related maturation of tau-aggregates was observed, initiated by the appearance of IC- and IN-tau, followed by the formation of pretangles exhibiting pT231-tau, pS396/pS404-tau and pS202/pT205-tau, then by MC1-conformational tau, and, finally, by the formation of Gallyas-positive NFTs. Since cases classified as nonAD [Braak NFT stages < I (including a-1b)] already showed IC- and IN-tau, our findings suggest that these lesions are a prerequisite for the development of AD.